Detecting and pyramiding target QTL for plant- and grain-related traits via chromosomal segment substitution line of rice - Mao, Zuyuan; Di, Xinyan; Xia, Saisai; Chen, Qian; Ma, Xiaohui; Chen, Mei; Yang, Zhenglin; Zhao, Fangming; Ling, Yinghua (Frontiers in Plant Science, 2022)
Plant height and grain length are important agronomic traits in rice, exhibiting a strong effect on plant architecture and grain quality of rice varieties. A novel rice chromosomal segment substitution line (CSSL), i.e. CSSL-Z1357, with significantly increased plant height (PH) and grain length (GL), was identified from CSSLs constructed by using Nipponbare as a receptor and a restorer line Xihui 18 as a donor. CSSL-Z1357 carried 9nine segments from Xihui 18, with average segment length of 4.13 Mb. The results showed that the long grain of Z1357 was caused by the increased number of surface cells and the length of the inner glume. Thirteen QTLs were identified via the F2 population of Nipponbare/Z1357, including three each for grain length (GL, qGL-3, qGL-6 and qGL-7) and plant height (PH, qPH-1, qPH-7 and qPH-12I), among which qGL-3 increased grain length by 0.23 mm with respect to the allele from Z1357. Additionally, three single- (S1 to S3), two double- (D1, D2), and 1one triple-segment (T1) substitution lines were developed in F3 via marker -assisted selection. Results showed that pyramiding the segments from Chr.3 (qGL-3 and qPH-3), Chr.6 (qGL-6 and qPH-6), and Chr.7 (Null and qPH-7) tended to result in better phenotype of increased GL and PH, and decreased grain width (GW), providing a potential basis for enhancing grain yield and quality in rice breeding.